2014
DOI: 10.1091/mbc.e14-07-1190
|View full text |Cite
|
Sign up to set email alerts
|

Complete canthi removal reveals that forces from the amnioserosa alone are sufficient to drive dorsal closure inDrosophila

Abstract: Laser microsurgery and computer tracking of embryo structures indicate that the morphogenetic process of Drosophila dorsal closure requires only forces generated by the amnioserosa tissue. Forces generated by both “zipping” of epidermal tissue at the canthi corners and the resulting actomyosin purse string curvature are not necessary for closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 44 publications
(104 reference statements)
8
52
0
Order By: Relevance
“…S2), arguing against inefficient closure as the basis for the late defects. The velocity of the LEs, defined as dH/dt averaged over the duration of closure, was 14±4 and 13±4 nm/s for Pvr heterozygous and homozygous mutant embryos, respectively, similar to published velocities (Hutson et al, 2003;Wells et al, 2014). Time-lapse imaging did however suggest faltering of zipping in some embryos, which was appreciated by projecting time series data as 2D images (Fig.…”
Section: Pvr Protein Expression In the As And Ectodermsupporting
confidence: 65%
“…S2), arguing against inefficient closure as the basis for the late defects. The velocity of the LEs, defined as dH/dt averaged over the duration of closure, was 14±4 and 13±4 nm/s for Pvr heterozygous and homozygous mutant embryos, respectively, similar to published velocities (Hutson et al, 2003;Wells et al, 2014). Time-lapse imaging did however suggest faltering of zipping in some embryos, which was appreciated by projecting time series data as 2D images (Fig.…”
Section: Pvr Protein Expression In the As And Ectodermsupporting
confidence: 65%
“…Without these forces, one or both morphogenetic processes fail. This final step is supported by previous experiments in which germband retraction and/or dorsal closure failed because amnioserosa structural integrity was disrupted by either laser ablation (Kiehart et al, ; Hutson et al, ; Toyama et al, ; Solon et al, ; Lynch et al, ; Wells et al, ) or widespread premature apoptosis (U‐shaped group mutants; Frank and Rushlow, ; GoldmanLevi et al, ; Lamka and Lipshitz, ).…”
Section: Discussionsupporting
confidence: 58%
“…For the latter two phenotypes, 17 of 19 embryos displaying one of the two defects also had holes at the earlier observation timepoint. Correlation is of course not causation, but previous work on the mechanics of both germband retraction and dorsal closure showed that the amnioserosa makes a critically important contribution to the forces driving those processes (Hutson et al, 2003;Toyama et al, 2008;Solon et al, 2009;Lynch et al, 2013Lynch et al, , 2014Wells et al, 2014). These processes can fail if the amnioserosa's structural integrity is compromised by means of laser ablation (Hutson et al, 2003;Lynch et al, 2013) or mutations (Frank and Rushlow, 1996;Reed et al, 2004); heat-shock-induced holes could do the same.…”
Section: Do Amnioserosa Holes Cause Subsequent Development Defects?mentioning
confidence: 99%
“…However, several lines of evidence suggest that a ratchet mechanism stabilising the contracted state of amnioserosa cells is acting at the level of individual cells (Blanchard et al, 2010;Wang et al, 2012;Wells et al, 2014). In particular, the analysis performed here of actin oscillatory dynamics in α-Cat mutants suggests that the increase in the expansion half-cycle of amnioserosa apical cell oscillations could be due to an increase in the time interval between the appearance of consecutive foci.…”
Section: Discussionmentioning
confidence: 73%